Relationship Power As a Mediator of Intimate Partner Violence and Mental Health Issues Among Incarcerated, Substance-Using Women. (March 2014) - Minieri, Alexandra M.; Staton-Tindall, Michele; Leukefeld, Carl; Clarke, Jennifer G.; Surratt, Hilary L.; Frisman, Linda K.
The purpose of this study was to examine perceived relationship power as a mediator of the relationship between intimate partner violence (IPV) and mental health issues among incarcerated women with a history of substance use. Cross-sectional data from 304 women as part of the Criminal Justice Drug Abuse Treatment Studies (CJ-DATS) were used to evaluate this hypothesis. Regression analyses examined the mediation relationship of perceived relationship power in the association between a history of IPV and mental health issues. Results supported the hypothesis, suggesting that perceived relationship power helps to explain the association between IPV and mental health issues. Implications of the findings for the provision of services to address the needs of these women are discussed, including assessment of perceived relationship power and focusing counseling interventions on women's experiences with power in intimate relationships.